The Backyard of Slavery: Child and Adolescent Slaves - Akkaya, Mustafa (Journal of History Culture and Art Research, 2020)
Slavery is a phenomenon as old as the history of humanity. In the Ottomans era a non-free person called slave or captive. As in many societies, there is not only in ottoman society slavery adult but also children and this real undeniable. In the related literature, it is not so possible to find out studies on child slaves compared to the studies on adolescent slaves. Child slaves were also the tragic fact of history like adult slaves. The employment of child slaves and the sale of them as a trade product is another problem. The child of a married slave is born as a slave. For this reason, child slaves are as old as the history of slaves. Additionally, slaves captured in the wars or gained as booty were also enslaved. One-fifth of captives gained in the war were used in palaces or army by Ottoman on the rules kul system. The rest was distributed to the war participants or the ones who succeeded in the war. Thus, slavery turned into a form of meeting the need of the state, a commodity, a money prize, or a workforce in society. This study aims to make a general assessment on child slaves in the Ottoman society. In this context, child slaves were analyzed in terms of being leakage, their physical properties, and their original homeland. For this study, court records (şer’iyye sicili) of İstanbul, Üsküdar, Galata, Balat, Kadıköy, Eyüp, Manisa, Bursa, Balıkesir, Tekirdağ (Rodoscuk) and Konya were used as main sources.